Genetic diversity studies of cumin (Cuminun cyminum L.) genotypes in western plains of Rajasthan - Kumhar, S. R.; Choudhary, B. R.; Ramesh, Ramesh; Mehriya, M. L. (Journal of Spices and Aromatic Crops, 2020)
Genetic diversity was studied on fifty-four genotypes of cumin, Cuminum cyminum L. at “Agricultural Research Station, Mandor, Jodhpur” during rabi season 2017-18. The mean squares were found significantly different for all the characters under study, depicting the availability of variability among the study materials. The high magnitude of phenotypic coefficient of variance (PCV) and genotypic coefficient of variance (GCV) for seed yield, primary branches per plant and number of umbels per plant depicted the presence of vast amount of variation for the character along with high heritability (68-97%) combined with higher genetic advances as percentage of means for seed yield. The highest intra-cluster distance was recorded in cluster VI (11.8) along with cluster VII (11.33) and cluster VIII (8.29) depicting large genetic variability among the genotypes of these three clusters. The highest inter-cluster distance was reported among cluster III and VIII (51.97) followed by cluster III and VII (40.07) and cluster IV and cluster VIII (34.77), suggesting wide range of diversity between genotypes of the clusters. Amongst the characters, seed yield contributed the highest towards genetic divergence (47.80%) followed by number of umbel per plant (25.65%), branches per plant (8.60%) and 1000 seed weight (6.64%).